2007
DOI: 10.1007/s11284-007-0404-x
|View full text |Cite
|
Sign up to set email alerts
|

Warming effects on growth and physiology in the seedlings of the two conifers Picea asperata and Abies faxoniana under two contrasting light conditions

Abstract: The short-term effects of two levels of air temperature (ambient and warmed) and light (full light and ca. 10% of full light regimes) on the early growth and physiology of Picea asperata and Abies faxoniana seedlings was determined using open-top chambers (OTC). The OTC manipulation increased mean air temperature and soil surface temperature by 0.51°C and 0.34°C under the 60-year plantation, and 0.69°C and 0.41°C under the forest opening, respectively. Warming, with either full-light or low-light conditions, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 37 publications
8
51
1
4
Order By: Relevance
“…The effects of experimental warming on P. asperata seedlings Agree well with the similar studies (Yin et al 2008;Danby and Hik 2007), artificial warming clearly increased total biomass accumulation of P. asperata seedlings without Means ± SE (n = 4) followed by different letters within rows are significantly different at the P \ 0.05 level. Significant effects of the two factors as well as of the interaction are indicated in the last three columns W warming effect, F nitrogen effect, W*F interaction effect of warming and nitrogen, Block block effect, ns not significant (P [ 0.05) *, **, *** indicate a significant difference between treatments at P \ 0.05, P \ 0.01, P \ 0.001, respectively Means ± SE (n = 4) followed by different letters within rows are significantly different at the P \ 0.05 level.…”
Section: Warming Effects Of Infrared Heaterssupporting
confidence: 85%
See 1 more Smart Citation
“…The effects of experimental warming on P. asperata seedlings Agree well with the similar studies (Yin et al 2008;Danby and Hik 2007), artificial warming clearly increased total biomass accumulation of P. asperata seedlings without Means ± SE (n = 4) followed by different letters within rows are significantly different at the P \ 0.05 level. Significant effects of the two factors as well as of the interaction are indicated in the last three columns W warming effect, F nitrogen effect, W*F interaction effect of warming and nitrogen, Block block effect, ns not significant (P [ 0.05) *, **, *** indicate a significant difference between treatments at P \ 0.05, P \ 0.01, P \ 0.001, respectively Means ± SE (n = 4) followed by different letters within rows are significantly different at the P \ 0.05 level.…”
Section: Warming Effects Of Infrared Heaterssupporting
confidence: 85%
“…A max reflected the rate of diffusion of CO 2 to Rubisco, the activity of Rubisco, and the rate of regeneration of RuBP (Farquhar et al 1980), and U is the efficiency of light utilization in photosynthesis. The positive effects of warming on photosynthesis have also been reported by other studies (Yin et al 2008;Saxe et al 2001). However, the positive effects of warming on photosynthesis only found under ambient nitrogen conditions.…”
Section: Warming Effects Of Infrared Heaterssupporting
confidence: 81%
“…The effects of warmer climate on aboveground forest ecosystems have already been studied with various techniques (Farnsworth et al 1995;Luxmoore et al 1998;Yin et al 2008;Danby and Hik 2007). However, a few studies have been conducted in situ on the effects of soil warming on belowground forest ecosystems, including the root growth and rhizosphere soil processes, using heating cables (Van Cleve et al 1990;Majdi and Ö hrvik 2004), *P < 0.05, ** P < 0.01, *** P < 0.001, NS not significant (significant difference between treatments) Dependent variable: total biomass.…”
Section: Warming Effectsmentioning
confidence: 99%
“…Our previous study results showed that warming increased photosynthetic rates and the aboveground biomass of dragon spruce (Picea asperata) seedlings (Yin et al 2008;Zhao and Liu 2009a), and nitrogen fertilization significantly improved plant aboveground growth (Zhao and Liu 2009a). However, it remained unclear whether belowground growth, root/shoot ratio, and carbon and nitrogen allocation above-and belowground will change consistently with aboveground parameters under warming, enrichment of soil N or a combination of both?…”
Section: Introductionmentioning
confidence: 99%
“…Climate envelope models and tree ring analyses imply suitable habitat is largely defined by climate variables (Littell et al 2010;Mckenzie et al 2003;Nitschke and Innes 2008). Additionally, growth and mortality of conifers are known to be sensitive to temperature, soil moisture (likely to decrease with warmer temperatures), and CO 2 (Fritts 1974;Gregg et al 2003;Handa et al 2006;Holman and Peterson 2006), particularly at seedling stages (Yin et al 2007). Recent studies demonstrate that tree mortality is increasing in western North America (van Mantgem et al 2009), raising the possibility of a sudden loss of adult trees.…”
mentioning
confidence: 99%